Division of neuromuscular compartments and localization of the center of the highest region of muscle spindles abundance in deep cervical muscles based on Sihler’s staining - Wang, Danli; Chen, Peng; Jia, Fangfang; Wang, Meng; Wu, Junxi; Yang, Shengbo (Frontiers in Neuroanatomy, 2024)
Purpose The overall distribution pattern of intramuscular nerves and the regions with the highest spindle abundance in deep cervical muscles have not been revealed. This study aimed to reveal neuromuscular compartmentalization and localize the body surface position and depth of the center of the region of highest muscle spindle abundance (CRHMSA) in the deep cervical muscles. Methods This study included 36 adult cadavers (57.7 ± 11.5 years). The curved line joining the lowest point of the jugular notch and chin tip was designated as the longitudinal reference line (line L), and the curved line connecting the lowest point of the jugular notch and acromion was designated as the horizontal reference line (line H). Modified Sihler’s staining, hematoxylin–eosin staining and computed tomography scanning were employed to determine the projection points (P) of the CRHMSAs on the anterior surfaces of the neck. The positions (PH and PL) of point P projected onto the H and L lines, and the depth of each CRHMSA, and puncture angle were determined using the Syngo system. Results The scalenus posterior and longus capitis muscles were divided into two neuromuscular compartments, while the scalenus anterior and longus colli muscles were divided into three neuromuscular compartments. The scalenus medius muscle can be divided into five neuromuscular compartments. The PH of the CRHMSA of the scalenus muscles (anterior, medius, and posterior), and longus capitis and longus colli muscles, were located at 36.27, 39.18, 47.31, 35.67, and 42.71% of the H line, respectively. The PL positions were at 26.53, 32.65, 32.73, 68.32, and 51.15% of the L line, respectively. The depths of the CRHMSAs were 2.47 cm, 2.96 cm, 2.99 cm, 3.93 cm, and 3.17 cm, respectively, and the puncture angles were 87.13°, 85.92°, 88.21°, 58.08°, and 77.75°, respectively. Conclusion Present research suggests that the deep cervical muscles can be divided into neuromuscular compartments; we recommend the locations of these CRHMSA as the optimal target for administering botulinum toxin A injections to treat deep cervical muscle dystonia.